WHAT CAUSES NON-PERFORMING LOANS? EVIDENCE FROM THE ISLAMIC BANKING SECTOR OF BANGLADESH - Chowdhury, Md. Asad Iqbal; Uddin, Mohammad Shamsu; Ullah, Habib; Ahmmed, Monir; Shadek, Md Jafar (International Journal of Accounting & Finance Review, 2023)
This study aims to investigate the impact of bank-specific and macroeconomic factors on non-performing loans (NPLs), also known as irregular loans, in Islamic banks in Bangladesh. The study is crucial, as the NPL has become a growing concern for Bangladesh’s banking sector, which is affecting the country’s economy. The data of banks specific factors were collected from the annual reports of the sample. In contrast, macroeconomic factors were gathered from the World Development Indicators covering the period from 2007 to 2018. Different diagnostic tests, including correlations, heteroskedasticity, and VIF (Variance Inflation Factor), were run to confirm that the results from OLS are accurate and reliable. The study further runs fixed effect and random effect models to check the robustness of the findings. The findings indicate that bank-specific factors such as loan growth, loan-to-asset ratio, and net interest margin significantly reduce NPLs. Moreover, macroeconomic factors like GDP growth and inflation significantly influence NPLs under all models. While we divide the samples into some sub-samples, we found almost similar results, confirming the robustness of the findings. The findings suggest banks’ management, regulatory bodies, and other stakeholders have necessary initiatives on how to reduce the NPLs. JEL Classification Codes: F65, G21, G32, H81.